2009
DOI: 10.2298/pif0901019m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper-based compounds, antibiotics and a plant activator on population sizes and spread of Clavibacter michiganensis subsp. michiganensis in greenhouse tomato seedlings

Abstract: SUMMARYThree copper-based compounds (copper hydroxide, copper oxychloride, copper sulphate), two antibiotics (streptomycin and kasugamycin) and a plant activator (ASM) significantly reduced population sizes and spread of C. michiganensis subsp. michiganensis among tomato seedlings in the greenhouse. Streptomycin had the best effect in reducing pathogen population size in all sampling regions. Moreover, this antibiotic completely stopped the spread of C. michiganensis subsp. michiganensis in the region most dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
4
0
4
Order By: Relevance
“…() determined the in vitro sensitivity of Cmm strains to streptomycin, reporting an MIC value of 6 μg mL −1 . The effect of streptomycin on tomato plants has been evaluated in Spain (de León et al ., ), Serbia (Milijasevic et al ., ) and the USA (Hausbeck et al ., ; Werner et al ., ) under greenhouse conditions. In these studies, streptomycin applications were shown to be effective, reducing the symptoms of bacterial canker.…”
Section: Discussionmentioning
confidence: 99%
“…() determined the in vitro sensitivity of Cmm strains to streptomycin, reporting an MIC value of 6 μg mL −1 . The effect of streptomycin on tomato plants has been evaluated in Spain (de León et al ., ), Serbia (Milijasevic et al ., ) and the USA (Hausbeck et al ., ; Werner et al ., ) under greenhouse conditions. In these studies, streptomycin applications were shown to be effective, reducing the symptoms of bacterial canker.…”
Section: Discussionmentioning
confidence: 99%
“…stewartii yang terdapat dalam benih walaupun belum mampu mengeliminasinya. Milijašević et al (2009) melaporkan bahwa streptomisin sulfat dengan konsentrasi 0.025% mampu mengurangi populasi patogen Clavibacter michiganensis subsp. michiganensis pada persemaian tomat di rumah kaca.…”
Section: Percobaan I: Penentuan Treatment Window Perlakuan Panas Keriunclassified
“…tomato, which continue evolving (Milijasevic et al, 2009a). The use of antibiotics has also been considered as ineffective against several pathogens and many countries do not permit its use.…”
Section: Introductionmentioning
confidence: 99%